Long-Term Outcomes of Percutaneous Coronary Intervention for Patients With In-Stent Chronic Total Occlusion Versus De Novo Chronic Total Occlusion. (September 2021) - Gao, Ke; Li, Bo-Lin; Zhang, Miao; Rong, Jie; Yang, Lei; Fan, Li-Hong; Liang, Qi; Wu, Wei; Feng, Zhe; Yang, Wan-Ying; Wu, Yue; Zheng, Xiao-Pu; et al.
Limited data are available on long-term outcomes and health status in the treatment of in-stent coronary chronic total occlusion (IS-CTO) and de novo coronary chronic total occlusion (de novo CTO). This study compared the long-term clinical outcomes and health status of percutaneous coronary intervention (PCI) for patients with IS-CTO versus patients with de novo CTO in the drug-eluting stent era. We screened 483 consecutive patients with 1 CTO lesion, including 81 patients with IS-CTO and 402 patients with de novo CTO. Propensity score matching was used to balance baseline characteristics between the 2 groups. The clinical end point was major adverse cardiac events (MACE). The success rates of CTO lesion revascularization were similar in both groups. In the propensity score-matched patients, after a median follow-up of 36 months, MACE was observed in 32.8% of patients with IS-CTO versus 13.5% of the patients with de novo CTO ( P < .001), mainly driven by target-vessel revascularization (21.9% vs 6.7%; P < .01). Moreover, patients with IS-CTO had significantly worse Seattle Angina Questionnaire anginal stability scores than the patients with de novo CTO. In conclusion, patients with IS-CTO after PCI had a worse clinical outcome, mainly MACE, and a poorer anginal stability in the long term than patients with de novo CTO.